A review of nitrogen translocation and nitrogen-use efficiency. (26th November 2019) - Xing, Yingying; Jiang, Wenting; He, Xiaolong; Fiaz, Sajid; Ahmad, Shakeel; Lei, Xin; Wang, Wenqiang; Wang, Yanfeng; Wang, Xiukang
Abstract: Nitrogen (N) is a primary nutrient for crop growth. In most agricultural areas, crop production relies heavily on the supply of exogenous N fertilizers. Globally, a large amount of nitrogenous fertilizer is applied to achieve maximum crop productivity. However, N fertilizer application is costly and negatively impacts the environment. One way around these problems is to provide a new N-use efficiency (NUE) framework that promotes the efficient acquisition and use of N and high N translocation rates from vegetative organs to reproductive organs under reduced N inputs. This review integrates the current knowledge about the direct and indirect effects of soil properties, crop varieties, soil water status, soil N fertilizers, and soil microbes on N translocation. In addition, we explore strategies that specifically accomplish N translocation via mycorrhizal fungi. Finally, we discuss recent advances in plant physiology, demonstrating that N translocation is an effective target to improve cereal yields and NUE. Although the relationship between crop variety and N translocation is mostly unknown, understanding this relationship is necessary to select and breed crop varieties that exhibit high yields and N translocation efficiency.